Skuteczność nauczania metodologii badań społecznych studentów pedagogiki - analizy panelowe = Teaching effectiveness of social research methodology in case of pedagogy students - panel analysis - Narkiewicz-Niedbalec, Ewa; Mianowska, Edyta (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The article attempts to diagnose teaching effectiveness of social research methodology in case of pedagogy students from the University of Zielona Gora. The authors analyse the educational standards of social research methodology valid in the education of educators. What is more, they address the issue of the indicators of its effectiveness. The students do a pedagogical methodology course on the first cycle studies and on the second cycle studies they do a methodology of the social sciences course, which broadens their knowledge of sociology and psychology.
Keywords: metodologia badań społecznych; szkolnictwo wyższe; kształcenie; standardy kształcenia; efektywność edukacji; badania